Network medical organizations: development strategy of and management peculiarities - A. V. Bobrovsky (Бюллетень сибирской медицины)
Advantages provided by network solutions in medicine are now being recognized at all management levels owing to the set of new possibilities, which can be reduced for simplicity to three key principles, namely, the presence of common information resources, replication of valid data from a common center, consolidation of data and information in a common center. Many network clinics using brand management technologies in their marketing strategies have achieveв significant success, which allows this version of strategy to be considered as optimal one.